1993
DOI: 10.1007/bf01967259
|View full text |Cite
|
Sign up to set email alerts
|

Absence ofHelicobacter pylori in dental plaques inHelicobacter pylori positive dyspeptic patients

Abstract: To test the validity of reports on detection of Helicobacter pylori in the mouth, samples were obtained simultaneously from the gastric mucosa and dental plaques for culture in 94 patients examined consecutively by endoscopy. Histological examinations and serological tests were also performed. Helicobacter pylori was not found in the mouth of any of the patients including 52 who had culture-positive gastric biopsies. Thus earlier results could not be confirmed, however, other techniques such as the polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…In humans, the incidence of Helicobacter pylori in the oral cavity ranges from 0% to 100% (Majmudar et al 1990, Bernander et al 1993, Agüloǧlu et al 2006, Cellini et al 2010. Such a discrepancy may be caused by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the incidence of Helicobacter pylori in the oral cavity ranges from 0% to 100% (Majmudar et al 1990, Bernander et al 1993, Agüloǧlu et al 2006, Cellini et al 2010. Such a discrepancy may be caused by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of unsuccessful attempts to culture H. pylori from the mouth [27,28] may be due to the organism being present in a non-culturable coccoid form, or as a transient member of the oral micro¯ora. However, detection by PCR indicates that the presence of H. pylori can be demonstrated in the mouths of a signi®cant number of infected individuals [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of RAS was based on accepted clinical criteria (16). The diagnosis of HSV infection was determined by serum examination (17 Discussion Culture is the gold standard for diagnosis of H. pylori infection (2,23), but it is very unlikely that oral H. pylori would be detected by culture (4,6,9). A low number of organisms or loss of viability during processing of dental specimens might contribute the poor sensitivity of culture (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…Today, it is considered to be a pathogen important to the development of gastrointestinal ulcers and it has been implicated as a carcinogen for gastric cancer and mucosa-associated lymphoid-tissue lymphoma of the stomach (2,3). H. pylori has been detected in dental plaque, saliva, and the subgingival region (4)(5)(6)(7)(8), and there have been reports that H. pylori strains in the mouth and stomach are identical (7,9,10). It has been suggested that the oral cavity might be an alternative reservoir for H. pylori (11,12).…”
Section: Introductionmentioning
confidence: 99%